2005
DOI: 10.1128/jvi.79.18.11925-11934.2005
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Activation of the Interleukin-2 Autocrine Loop through the Nuclear Factor of Activated T Cells by Nonleukemogenic Human T-Cell Leukemia Virus Type 2 but Not by Leukemogenic Type 1 Virus

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) but not HTLV-2 is associated with adult T-cell leukemia. We found that HTLV-2 Tax2 protein stimulated reporter gene expression regulated by the interleukin (IL)-2 promoter through the nuclear factor of activated T cells (NFAT) in a human T-cell line (Jurkat). However, the activity of HTLV-1 Tax1 was minimal in this system. T-cell lines immortalized by HTLV-2 but not HTLV-1 constitutively exhibited activated NFAT in the nucleus and constitutively expressed IL-2 mRNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…In contrast to Tax1⌬C, the transforming activity of Tax2B without the PBM was augmented by an active NIK. Previous studies have reported that Tax2 but not Tax1 strongly activates NFAT, and this activity is important for Tax2-mediated transformation of CTLL-2 cells (21,31). Therefore, NFAT activation may play a role in the augmentation of Tax2B's transforming activity by active NIK.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to Tax1⌬C, the transforming activity of Tax2B without the PBM was augmented by an active NIK. Previous studies have reported that Tax2 but not Tax1 strongly activates NFAT, and this activity is important for Tax2-mediated transformation of CTLL-2 cells (21,31). Therefore, NFAT activation may play a role in the augmentation of Tax2B's transforming activity by active NIK.…”
Section: Discussionmentioning
confidence: 98%
“…SLB-1 and ILT-Koy are HTLV-1-positive human T-cell lines. PBL01 and PBL2 are HTLV-2-positive human T-cell lines (31). Jurkat, SLB-1, and CTLL-2/Tax1 were cultured in RPMI 1640 medium supplemented with 10% fetal bovine serum (FBS) (RPMI-10% FBS).…”
Section: Methodsmentioning
confidence: 99%
“…IL-13 stimulation by an HTLV Tax-responsive NFAT site Tax, has little or no impact on NFAT activation required for the stimulation of an NFAT-dependent promoter (Niinuma et al, 2005). The low but detectable levels of NFAT1 protein in the nuclei of all HTLV-transformed cells tested in this and other studies (Niinuma et al, 2005;Sharma et al, 2002) could be due to expression of the HTLV-1 p12(I) protein, which could enhance NFAT activation by increasing cytoplasmic calcium (Yasunaga & Matsuoka, 2007). Additionally, differentiation or transformation-specific activation of the cells could contribute to NFAT activation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several reports have shown that Tax-1 and Tax-2 have distinct biological properties (30)(31)(32)(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%